2018
DOI: 10.18203/2320-1770.ijrcog20182506
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of gestational diabetes mellitus among pregnant mothers admitted in gynaecology/obstetrics ward of Sheikh Zayed Hospital Rahim Yar Khan, Pakistan

Abstract: Background: The gestational diabetes mellitus (GDM), defined as my degree of glucose intolerance with onset of first recognition during pregnancy, is poorly understood due to low socioeconomic dynamics among the pregnant mothers of Rahim Yar Khan. It results in many maternal and fetal complications. This study was carried out to determine the frequency and socio- demographic profile of pregnant mothers with gestational diabetes mellitus admitted in Gynecological Obstetrics wards of Sheikh Zayed Medical College… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In Pakistan, a study concluded on the prevalence of GDM, it was observed that more than one in every 10 pregnant mothers has gestational diabetes mellitus. [5] The ACOG recommended 150 minutes/week exercise for post-partum and non-complicated pregnancies. This can reduce the risk of spasms, edema, and shortness of breath and back pain etc.…”
mentioning
confidence: 99%
“…In Pakistan, a study concluded on the prevalence of GDM, it was observed that more than one in every 10 pregnant mothers has gestational diabetes mellitus. [5] The ACOG recommended 150 minutes/week exercise for post-partum and non-complicated pregnancies. This can reduce the risk of spasms, edema, and shortness of breath and back pain etc.…”
mentioning
confidence: 99%